Analisis Laporan Keuangan untuk Menilai Kinerja Keuangan Perusahaan Tahun 2018 – 2024 - Maulidia, Sarah; Sihabudin; Robby Fauji (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research on plans to take a gander at monetary reports with respect to the improvement of exhibition of agribusiness organizations recorded on the Indonesia Stock Trade throughout recent years from 2018 to 2022 utilizing Current Ratio (CR), Quick Ratio (CR), Debt to Assets Ratio (DAR), Debt to Equity Ratio (DER) Net Profit Margin (NPM), Return On Assets (ROA),, Return On Equity (ROE), Total Assets Turnover (TATO) Fixed Assets Turnover (FATO),. Overall, the research reveals that agricultural companies listed on the Indonesia Stock Exchange have varying financial ratios, with some having very high ratios and others having very low ratios.